Crip colony mestizaje, US imperialism, and the queer politics of disability in the Philippines - Coráñez Bolton, Sony 1985- (New York Duke University Press, 2023)
"Crip Colony is an interdisciplinary analysis of the racial politics of disability, mestizaje, and sexuality in the Philippines. Sony Coráñez Bolton reads across language archives and overlapping Spanish and US imperialisms, drawing on colonial records, visual culture, poetry, presidential speeches, travel narratives, and political essays, in addition to the famous Spanish-language Filipino novel Noli Me Tangere. Through these texts he shows how these imperial and racial regimes were also regimes of ability. Expanding traditional engagements with mestizaje, Coráñez Bolton examines the ways that Filipinx mestizaje became a eugenic framework which identified native Filipino subjects as inherently disabled, in need of reform and rehabilitation, and mixed-race Filipinos as able to offer a form of "benevolent rehabilitation" which would prepare these deficient natives for assimilation into the US empire. Through this crip critique of coloniality, Coráñez Bolton shows how mestizaje allowed for "superior" mixed-race subjects to govern the archipelago in collusion with imperial processes of dispossession and debilitation"--
Crip colonial critique : reading mestizaje from the Borderlands to the Philippines -- Benevolent rehabilitation and the colonial bodymind : Filipinx American studies as disability studies -- Mad María Clara : the queer aesthetics of mestizaje and compulsory able-mindedness -- Filipino itineraries, orientalizing impairments : Chinese foot-binding and the crip coloniality of travel literature -- A colonial model of disability : running amok in the mad colonial archive of the Philippines -- A song from Subic : racial disposability and the intimacy of cultural translation.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Imperialism; People with disabilities in mass media; Queer theory; Multiracial people -- Philippines; Sociology of disability -- Political aspects; Philippines -- Colonization